1997
DOI: 10.1530/eje.0.1370459
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant human GH replacement therapy on lipoprotein(a) and other lipid parameters in adults with acquired GH deficiency: results of a double-blind and placebo-controlled trial

Abstract: The effect of GH substitution on serum lipids and lipoproteins, and in particular lipoprotein(a) (Lp(a)), was investigated in 32 adults with postoperative (acquired) GH deficiency as part of a double-blind, placebo-controlled trial. Seventeen men and fifteen women, aged 18-59 years (mean 42 years) from two centres (Hannover and Göttingen) were randomly assigned to two groups. Group P (placebo) received placebo for the first 12 months and recombinant human GH (rhGH) for the following 12 months (open phase). Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
3
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
2
21
3
1
Order By: Relevance
“…There is concern that GH increases the concentration of atherogenic Lp(a) particles [34,35]. In contrast to these shorter term observations, in the present study, levels only rose transiently during GH therapy, and, in the long term, did not signi®cantly increase with GH.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…There is concern that GH increases the concentration of atherogenic Lp(a) particles [34,35]. In contrast to these shorter term observations, in the present study, levels only rose transiently during GH therapy, and, in the long term, did not signi®cantly increase with GH.…”
Section: Discussioncontrasting
confidence: 87%
“…Several, for the most part controlled, studies have reported favourable lipolytic and anabolic eects of GH treatment in PWS, improving lipid metabolism [11] and body composition during 12 months [16,17,31,32]. While it has also been shown in children with GH de®ciency [28] or Turner syndrome [44], that GH decreases LDL-cholesterol (LDL-C) and increases high density lipoprotein cholesterol (HDL-C) during GH treatment, this favourable eect might be counteracted by an increase in lipoprotein (a) (Lp(a)), which independently is associated with a high risk for arteriosclerosis [34,35]. In addition, the long-term eects of GH on lipid metabolism have not yet been studied in PWS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Acromegalics have elevated plasma Lp(a) levels, and successful treatment of this disorder is associated with a decrease in plasma apo(a) levels proportional to the reduction in GH. 16,15,36 GH administration to adult individuals with GH deficiency result in a 30% to 200% increase in plasma Lp(a) levels. 32,37 A significant increase in plasma apo(a) level also occurs when GH is given to normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…Em resposta à reposição de GH, o principal achado é uma redução nos níveis de colesterol total e LDL colesterol, que em alguns dos estudos foi correlacionado com as concentrações basais de LDL colesterol (21,(25)(26)(27)(28). GH aumenta a secreção hepáti-ca de VLDL e induz a expressão de receptores hepáti-cos de LDL, promovendo o clearance de VLDL/LDL da circulação (29)(30)(31).…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified